Analysis of the IgE network: Inhibition of CD23-mediated IgE upregulation and CD21/C3d interaction - Yahya, M; MOHD NORHAKIM YAHYA (2011)
Allergic reactions are mainly mediated by the interactions between the IgE and its ligands, amongst them CD23 and CD21 in what is termed the IgE network. CD23 is involved in upregulating IgE expression by forming a trimolecular complex with CD21 and IgE on the B-cell surface, resulting in the specific activation of IgE-positive B cells. CD21 also interacts with C3d and is a bridge between the innate and the immune system. A crystal structure of the interaction has been solved (Szakonyi et al., 2001) but was controversial because it contradicted previous biochemical analyses. The aims of this thesis were to use various biophysical techniques to study the interactions between the molecules in the IgE network and its possible inhibition. Part 1: Characterisation of a phage display-derived peptide that inhibit IgE binding to CD23 A peptide was previously derived using phage display technology and tested for binding ability to CD23 using SPR and ITC. Subsequent NMR experiments were performed to identify the binding site, followed by characterization of its derivatives. Crystallisation of CD23 with the peptide and soaking with its truncated tripeptide, NWP, were also attempted. Part 2: Characterisation of CD23 and its interaction with its ligands X-ray crystallography was undertaken to solve the structure of derCD23 in complex with a phage display-derived peptide (Part1) followed by crystal soaking with a truncated tripeptide, NWP. However, a reproducible, high-resolution wild type derCD23 structure was determined at 1.9 Å. A comparison of the binding behaviour between the monomeric derCD23 and a trimeric CD23 construct was carried out in order to see the effect of oligomerisation upon IgE binding. Using the known interaction map as well as a crystal structure, the possible interacting residues between CD23 and IgE were examined. The characterisation of the CD23/CD21 interaction was continued from previous efforts in order to confirm that the binding epitope of CD23 for CD21 lies within the C-terminus of CD23. Characterisation of the interactions of CD23/IgE/FcεRI was performed to examine these multimolecular interactions and possible regulatory mechanisms in mast cell degranulation. It was shown that CD23 can form multimeric complexes with IgE-Fc that bind to FcεRI with higher apparent affinity than IgE-Fc alone, which may lead to increases in mast cell degranulation. It was also found that the IgE bound on FcεRI still binds to CD23 although with a lower binding capacity, presumably due allosteric changes. The binding of CD23 with a monoclonal antibody IDEC-152 was also characterised using SPR and NMR spectroscopy. It was proposed that IDEC-152 might interfere with the trimerisation site of CD23 thus reducing its affinity for IgE. A thermofluor assay was developed and optimised for potential screening of compounds that bind to derCD23 using a qPCR machine, which may be useful to screen compounds that bind to CD23 as part of future drug discovery project. Crystallisation of the derCD23/CD21 and IgE/triCD23/CD21 complexes was also attempted as part of ongoing crystallisation projects. Part 3: The interaction between C3d and CD21 The interaction between C3d and CD21 is believed to be a bridge between the innate and adaptive immune response, and is thought to be pivotal in the initiation of autoimmune disease. Following from previous studies on this interaction, further characterisations were performed using NMR and ITC to confirm the involved sites on CD21 (SCR1-2) in binding to C3d. Several potential salt bridges have been identified so far, allowing a high-resolution docked structure of the C3d/CD21 complex.